A survey of the disaster management and recovery preparedness of the National Archives of the Philippines - Tiangco, Blas Ople G. (School of Library and Information Studies, University of the Philippines Diliman, 2000)
The field of archival management, in relation to conservation, preservation and restoration has yet to be fully recognized in our country. And in line with the growing volume of archives, there has been no attempt to conduct a survey of disaster management and recovery preparedness.